Pollen-Based Maps of Past Regional Vegetation Cover in Europe Over 12 Millennia—Evaluation and Potential - Githumbi, Esther; Pirzamanbein, Behnaz; Lindström, Johan; Poska, Anneli; Fyfe, Ralph; Mazier, Florence; Nielsen, Anne Brigitte; Sugita, Shinya; Trondman, Anna-Kari; Woodbridge, Jessie; Gaillard, Marie-José (Frontiers in Ecology and Evolution, 2022)
Realistic and accurate reconstructions of past vegetation cover are necessary to study past environmental changes. This is important since the effects of human land-use changes on biodiversity and climate are still under debate. Over the last decade, development, validation, and application of pollen-vegetation relationship models have made it possible to estimate plant abundance from fossil pollen data at both local and regional scales. The REVEALS model has been applied to produce datasets of past regional plant cover at 1◦ spatial resolution at subcontinental scales. However, such reconstructions are spatially discontinuous due to the discrete and irregular geographical distribution of fossil pollen record sites. Therefore, spatial statistical models have been developed to create continuous past plant cover maps using the REVEALS-based land cover estimates. We present the first continuous time series of spatially complete maps of past plant cover across Europe during the Holocene ( 11.7 k BP to present in 25 time windows). We use a spatial statistical model for compositional data to interpolate REVEALS-based estimates of three major land-cover types (LCTs: evergreen trees, summer-green trees and open land (grasses, herbs and shrubs)); producing spatially complete maps of the past coverage of the LCTs. The spatial model uses four auxiliary data sets — latitude, longitude, elevation and independent scenarios of past anthropogenic land-cover change based on per-capita land-use estimates— to improve model performance for areas with complex topography or few observations. We evaluate the resulting reconstructions for selected time windows using present day maps from the European Forest Institute, cross validate, and compare the results with earlier pollen-based spatially-continuous estimates for five selected time windows, i.e. 100 BP-present, 350–100 BP, 700–350 BP, 3.2–2.7 k BP and 6.2–5.7 k BP. The evaluations suggest that the statistical model provides robust spatial reconstructions. From the maps we observe the broad change in the land-cover of Europe from dominance of naturally open land and persisting remnants of continental ice in the Early Holocene to a high fraction of forest cover in the Mid Holocene, and anthropogenic deforestation in the Late Holocene. The temporal and spatial continuity is relevant for land-use, land-cover, and climate research.